Coisário cassino museu: no entre-espaço de um cassino extinto e um museu em processo - Marconi Drummond Lage (2024)
Through different visual poetics, this research is situated at the interrelation between art, curatorship, history, and contemporary museology, positioning itself at the interspace between an extinct casino and a museum, and anchored to the historical landmarks that forged the transformation of the modernist building – originally a casino – into a museological institution – the Museu de Arte da Pampulha [Pampulha Art Museum]. Part of the investigation is dedicated to the survey of historical, documental, iconographic, videographic, and artistic collections for the creation of a repository, here entitled “thingery-casino-museum”. In the interpolation between past and present and in the tracking of “things” accumulated, stored, forgotten, misplaced, and recovered, the investigation is coupled with the micro-histories in confrontation with the official historiography. To consolidate this ingenuity, the research adopts a digital collection creation system, equipped with customizable features. Autonomously, this archive/inventory, being flexible, mutates into a “display device”, promoting wanderings and connections among the collected “things” and their “thingnesses”. The work results in the formulation of two congruent writing systems that run parallel and are complementary to one another: the “thingery-casino-museum” repository and the volume containing the thesis. In addition to the construction of the “thingery”, the study prospects curatorial projects held at the Pampulha Art Museum throughout my professional career, between 2006 and 2010. Understood as an artistic experimentation, the thesis, managed by the artist-curator-collector, reflects on the power of previously collected images – rarefied and ephemeral – in order to disturb the interstitial history of an extinct casino that unfolds into a surviving museum, in a continuous process of (re)(de)construction.